2012
DOI: 10.1590/s1415-790x2012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Vigilância de eventos adversos a medicamentos em hospitais: aplicação e desempenho de rastreadores

Abstract: Os eventos adversos a medicamentos (EAMs) são causa importante de comprometimento da qualidade da atenção ao paciente hospitalizado e, por isso, devem ser identificados e caracterizados. Para tanto surgiram listas de rastreadores, entre elas a proposta pelo Institute for Healthcare Improvement. Aqui é apresentado o processo da aplicação dos rastreadores e o seu desempenho em um hospital de ensino. As informações sobre os rastreadores e os EAM foram coletadas por meio de revisão retrospectiva dos prontuários de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
22

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 17 publications
4
21
0
22
Order By: Relevance
“…The incidence of adverse drug events in this study was similar to that found in other studies: Switzerland (15.4%), England (15.8%) and United States (16.4%) 4,40,44 . Brazilian studies conducted by Rozenfeld et al 45 , Roque & Melo 46 , Giordani et al 47 and Reis & Cassiani 23 identified the occurrence of adverse drug events, with frequencies between 7% and 15.6%, similar to that of this study. These studies 23,45,46,47 were based on the approach proposed by IHI 25 , using trigger tool, showing reproducibility in other contexts.…”
Section: (24 Days Of Icu Stay) the Relationship Betweensupporting
confidence: 88%
See 1 more Smart Citation
“…The incidence of adverse drug events in this study was similar to that found in other studies: Switzerland (15.4%), England (15.8%) and United States (16.4%) 4,40,44 . Brazilian studies conducted by Rozenfeld et al 45 , Roque & Melo 46 , Giordani et al 47 and Reis & Cassiani 23 identified the occurrence of adverse drug events, with frequencies between 7% and 15.6%, similar to that of this study. These studies 23,45,46,47 were based on the approach proposed by IHI 25 , using trigger tool, showing reproducibility in other contexts.…”
Section: (24 Days Of Icu Stay) the Relationship Betweensupporting
confidence: 88%
“…However, just as in other studies 23,47 , in this study, we used the Naranjo et al 26 algorithm in order to evaluate the causality of adverse drug events. The use of this algorithm reduced judgment subjectivity in the consensus meetings.…”
Section: (24 Days Of Icu Stay) the Relationship Betweenmentioning
confidence: 99%
“…Um atributo que colaborou para o processo de captação de EAM foi a utilização da Ficha para Coleta de Medicamentos 16 . Esta permitiu visualizar e acompanhar a evolução do tratamento medicamentoso ao longo do tempo, além de relacionar os medicamentos com os parâmetros laboratoriais e evolução do paciente.…”
Section: Discussionunclassified
“…O uso desses rastreadores foi incorporado com base em revisão da literatura a qual os apresentou como capazes de identificar eventos relacionados ao uso de medicamentos 17 . Os medicamentos prescritos durante o período estudado foram registrados em Ficha para Coleta de Medicamentos 16 . Nesta ficha pôde ser acompanhado o período no qual o medicamento permaneceu prescrito e os dias em que foi utilizado.…”
Section: Artigo Originalunclassified
See 1 more Smart Citation